Soil science within German cities - Burghardt, Wolfgang; Kneib, Wolfram D.; Höke, Silke; Lehmann, Andreas; Makowsky, Lutz; Kocher, Birgit; Steinweg, Bernd (Journal of plant nutrition and soil science, 2022)
The soils of urban areas were belatedly discovered as a research subject, becoming popular for study in the 1970s. With the growth of cities, there were increased requirements for urban soil information to assure the urban quality of life. Thus, the WG Urban Soils (AKS [Arbeitskreis Stadtboeden], today AGUB) within the German Soil Science Society (DBG) was established in 1987. This paper outlines the national and international achievements of AKS/AGUB and the initiated international urban soil network. Particular attention is given to soil mapping and research in Germany. The foundation of AKS/AGUB initiated a high scientific response on the new research field of urban soils. A soil mapping instruction was established. According to the German concept of soil unit “soil form” from the substrate and soil formation, much attention was given to soil material of natural and technic origin, as well as structure and profile composition. The focus of soil formation is on the young age, the effect of artificial landscape construction, and the speed of soil development. For surveying areas of high soil diversity, conceptual maps were developed. A great number of cities were mapped. As in Germany, urban soils were included in several national soil classification systems. Those of Germany, the United States, Russia, France, and the international World Reference Base for Soil Resources (WRB) are compared. A great number of tasks of urban administration concern soil problems, such as pollution, soil sealing, urban greening, stormwater infiltration, heating, dust, and carbon sequestration, so soils were relevant in city government work. Internationally, the WG SUITMA of International Union of Soil Science and the US WG INCOMANTH were dedicated to urban soils. The AKS/AGUB could contribute to the European Commission with concepts of soil functions and soil evaluation and the introduction of Technosols to the WRB. Important future aspects will be the competition of intense rising soil consumption by building activities, and the availability and quality of soils for a sustainable urban life.